Interactions of cranial helminths in the European polecat (Mustela putorius): Implications for host body condition. (August 2022) - Frantz, Alain C.; Cantú Salazar, Lisette; Müller, Franz; Steinbach, Peter; Wittische, Julian; Heddergott, Mike
Abstract: Multiple helminth species commonly co-occur within mammals and their interactions may negatively affect the survival and breeding success of their hosts. However, it has been difficult to prove competition or mutualism between co-infesting helminths in field studies of wild mammals. The sinus cavities of European polecats ( Mustela putorius ) can be parasitised by the trematode Troglotrema acutum and the nematode Skrjabingylus nasicola and both helminths can co-occur within hosts. While both parasites can damage the host's bone structure and cause severe pathologies, their impact on host body condition is unclear. It is also unknown whether both parasites interact and how this might affect cranial damage and host body condition. We examined 515 fresh polecat skulls for the presence of both helminths and measured the hosts' amount of kidney perirenal fat as a measure of body condition. Our results demonstrated that, in addition to a host-intrinsic fixed factor (sex) and random factors accounting for spatial and temporal stochasticity, the helminths influenced each other's presence. Infestation with T. acutum increased the probability of catching S. nasicola with increasing age of the host, while males already infested with S. nasicola were more likely to become infested with T. acutum than females infested with the nematode. While we speculate that both effects resulted from parasite-induced behavioural alterations (increased foot consumption), it is not clear why, in the latter case, this effect would be stronger in males than females. We showed that the abundances of both parasites had significant positive effect on the likely presence of skull damage and a significant negative effect on the predicted presence of kidney fat. Given the evolutionary arms race that both host-parasite systems have undergone, it appears unlikely that either helminth played a significant factor in the population decline of the polecat in Europe. Graphical abstract: Image 1 Highlights: We provide evidence for interactions between co-infesting helminths in a wild mammal. Troglotrema acutum and Skrjabingylus nasicola can co-occur in the skulls of polecats. Infestation with one parasite can increase the probability of infestation with the other one. Heavy infestation with either helminth may have a negative effect on host body condition. Co-infestation does not change the severity of the parasites' clinical impact.